METHODOLOGY OF TEACHING FOREIGN LANGUAGES ACCORDING TO DEVI'S IDEAS - Khidirova Ibodat Niyozalievna (Scholar Express Journal, 2024)
The article describes useful techniques of teaching foreign languages according to dewey’s ideas. Many scientists have done researches on this topic as well as John Dewey,one of the most talented researchers in the history of modern educational theory. All the life he supported progressive education where a child-centered approach to education places the emphasis of learning on the needs and interests of the child
Keywords: education; approach; method; technique